CONDITION ASSESSMENT OF STUDENT HOSTEL BUILDING ON CAMPUSES OF FEDERAL UNIVERSITIES IN NORTH-CENTRAL NIGERIA - Anita Dzikwi ADAMU; Winston SHAKANTU (Journal of Construction Project Management and Innovation)
Universities and many tertiary educational institutions in Nigeria are under pressure to preserve their built environment. The focus of this study is to assess the condition of on-campus hostel buildings at Nigerian public universities with the aim of generating information about the maintenance requirement of the buildings. Condition assessment is the most common method for measuring building performance and identifying maintenance needs of facilities. In the process, the efficiency of the current maintenance management strategies is determined. Primary data were generated with the aid of a condition survey guide and rating sheets. The results were computed in percentages and presented on bar charts. The assessment results revealed the conditions of the components within the hostel building at the three universities studied. The walls, floors and ceilings of the most of enclosed spaces such as the bedrooms, kitchens and washrooms are in various degrees of deterioration. In most of the bedrooms, there are minor cracks and worn-out finishing with evidence of inadequate routine maintenance. There are many doors and windows with major problems such as damaged locking devices or door handles. Cracked or broken window panes and door panels are common. The toilets and bathroom facilities are almost not operational and are in need of urgent major maintenance works. The building facades ( ceilings, walls and floors) in the male and female hostels at university C are in good condition, signifying that the surfaces of the facades show slight soiling or discolorations or fading that affects mainly the aesthetic value of the buildings. Generally, the electrical and plumbing services at the hostels across all the universities studied are in poor conditions, some of the facilities were rated unsuitable for use.